Asymmetric electromagnetic shielding performance based on spatially controlled deposition of nickel nanoparticles on carbon nanotube sponge. (July 2022) - Zhang, Jiapeng; Zhu, Dejun; Zhang, Sheng; Cheng, Hao; Chen, Shuanglu; Tang, Rujun; Hang, Zhi Hong; Zhang, Tianhui; Zhang, Xiaohua; Yang, Zhaohui
Abstract: Nowadays, the secondary reflection of electromagnetic waves (EMWs) emitted from various metal-based electromagnetic interference (EMI) shielding materials has produced serious health problems on human being. Therefore, efficient shielding materials with high EMI shielding performance but low reflection are highly expected. Here, we report a flexible Ni@CNTS/CNTS/PDMS composite with a designed asymmetric structure exhibits a unidirectional EMI shielding performance with controlled magnetic permeability, conductivity and enhanced mechanical property. The maximum EMI shielding effectiveness (SE) measured in the X band (8–12 GHz) is greater than 70 dB with the low average reflection shielding effectiveness (SER ) of only 3.1 dB and the minimum reflection loss of about 0.71 at 12 GHz. The total EMI SE as well as the ratio of the adsorption to reflection is dominated by the amount of Ni particles and can be tuned by the Ni-deposition time. More interestingly, the asymmetric electro-magnetic structure leads to totally different EMI shielding performance with respect to wave incident direction: The reflection of EMWs at the nickel side is 17% lower than that at the bare CNTS side, while the total EMI SE value remains constant around 70 dB. Our findings provide a feasible and convenient strategy to reduce the reflection of highly conductive materials and precisely control the reflection to absorption ratio of EMI shielding materials. Graphical abstract: Image 1